A microwave-heated infrared reaction cell for the in-situ study of heterogeneous catalysts - Silverwood, Ian; McDougall, Gordon; Whittaker, Gavin (Ciencia, 1970)
A transmission infrared microreactor cell which holds a catalyst pressed disc in a controlled atmosphere and allows microwave and conventional heating up to 423K is demonstrated using the oxidation of carbon monoxide over the standard catalyst, EUROPT- 1. Optical characteristics are determined by the choice of CaF2, as the window material, allowing transmission from 77000- 1000cm-1. An oscillating microwave power heating regime with a peak height of 200W is used and time-resolved infrared spectra and mass spectrometry show oscillations in the reaction which correspond to the microwave heating.